A novel V-shaped layout method for VIV hydrokinetic energy converters inspired by geese flying in a V-Formation. (1st September 2021) - Zhang, Baoshou; Mao, Zhaoyong; Wang, Liang; Fu, Song; Ding, Wenjun
Abstract: A novel bio-inspired V-shaped layout is proposed to enhance energy conversion performance for VIV hydrokinetic energy converters. The layout method is inspired by wild geese flying in a V-formation. In this paper, 2-dimensional RANS equations with the SST k- ω turbulence model are used to simulate the VIV responses at various distances. The numerical method is verified by comparing with experiments. Two-cylinder and five-cylinder V-shaped layout are investigated separately to analyze multi-cylinder interactions. The main conclusions are: (1) The VIV response of the upstream cylinder is suppressed due to the blockage effect when at small distance. (2) The energy recovery area of downstream cylinders is identified and located on the edge of the wake. (3) In the energy recovery area, the enhancement mechanism of this novel layout is the upstream and downstream vortices coalesce, resulting in a significant increase in lift force on the downstream cylinder. (4) The converted power of downstream cylinders in the energy recovery area is increased by up to 6.3%–8.4%. Future work is directed to optimize the distance among the cylinders for optimal energy conversion. Highlights: A novel bio-inspired V-shaped layout for VIV energy converters is proposed. The VIV response of the upstream cylinder is suppressed due to blockage effects. Energy Recovery Area of downstream cylinders is located on the edge of the wake. The enhancement mechanism of Energy Recovery Area is the vortices coalescence. The converted power in the novel layout can be increased by up to 6.3%–8.4%.